Exploring The Psychological Impact of Miscarriage on Women - Navabinejad, Shokouh; Rizzo, Amelia; Kiliçaslan, Fethiye (Psychology of Woman Journal, 2024)
Objective: This study aims to provide a comprehensive qualitative analysis of the psychological impact of miscarriage on women, highlighting their emotional responses, physical experiences, social and relational impacts, and coping strategies. Methods and Materials: A qualitative research design was employed, utilizing semi-structured interviews with 28 women who have experienced one or more miscarriages. Participants were selected through purposive sampling to encompass a diverse range of ages, socioeconomic statuses, and backgrounds. Interviews were transcribed verbatim, and thematic analysis was conducted to identify and explore key themes and subthemes. Findings: The study revealed four main thematic categories: Emotional Response, Physical Experience, Social and Relational Impact, and Coping Mechanisms. Participants reported a spectrum of emotional responses, including grief, anxiety, and isolation, compounded by physical recovery challenges. Social and relational dynamics were significantly affected, with changes in relationships and a noted lack of support. Women employed a variety of coping mechanisms, from seeking information and resources to relying on professional support. The findings underscore the complexity of the miscarriage experience and the varied strategies women use to navigate their recovery. Conclusion: Miscarriage exerts a significant psychological toll on women, affecting their emotional well-being, physical health, social relationships, and coping abilities. This study emphasizes the need for holistic support systems that address the multifaceted nature of miscarriage’s impact. Healthcare providers and support networks play a crucial role in offering compassionate care and understanding, tailored to the individual experiences and coping styles of women.